Peran Hukum Adat Melayu dalam Penataan Masyarakat Multikultural di Kota Medan - Maharani, Suci; Nainggolan, Rusni Harianti; Harahap, Herlina Hanum (IAI Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the role of Malay customary law in structuring multicultural society in Medan City. As a city with high ethnic and cultural diversity, Medan City is a concrete example of how customary law can function as a unifying instrument within the framework of multiculturalism. This research uses a qualitative approach with a case study method to explore various aspects of Malay customary law as applied in people's daily lives, as well as their impact on harmonizing relations between ethnic groups. The research results show that Malay customary law has an important role in creating social balance through principles that prioritize deliberation, mutual respect and justice. However, there are challenges in implementing customary law in line with the influence of developments in state law and globalization which is increasingly strengthening. The conclusion of this research is that Malay customary law remains relevant in supporting the structuring of a multicultural society, but there needs to be adaptation and collaboration with the formal legal system to achieve better social integration.